1986
DOI: 10.7863/jum.1986.5.10.563
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of liver, spleen, and splanchnic vessels following partial liver resection.

et al.

Abstract: The liver and spleen size and the splanchnic vessel caliber were evaluated by means of real‐time ultrasonography in 12 consecutive patients who underwent a partial hepatic resection for benign or malignant lesions. All parameters were evaluated before surgery and 14 days, 28 days, two months, and six months after the partial hepatic resection. The liver size, which was halved after the resection, progressively increased during the follow‐up. The splanchnic veins showed, at 14 and 28 days, a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There are no data published after transplantation addressing the issue of adaptive liver growth. Surprisingly, an extensive MEDLINE search revealed only one paper dealing with this question: for patients with a liver tumor and hemihepat‐ectomy, Zoli (10) demonstrated that liver size progressively increased during a follow‐up of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data published after transplantation addressing the issue of adaptive liver growth. Surprisingly, an extensive MEDLINE search revealed only one paper dealing with this question: for patients with a liver tumor and hemihepat‐ectomy, Zoli (10) demonstrated that liver size progressively increased during a follow‐up of 6 months.…”
Section: Discussionmentioning
confidence: 99%